Osteoclasts are multinucleated cells that degrade cartilage as well as bone - Larrouture, QC (2019)
Osteoclasts are essential for bone remodelling and are normally found at the bone surface where they create resorption pits. Osteoclasts are present in diseased cartilage in osteoarthritis and rheumatoid arthritis as well as in primary bone sarcomas including osteosarcoma, giant cell tumour of bone and osteochondroma. Whether osteoclasts can also degrade cartilage has been little explored. The aim of this thesis was to characterise how osteoclasts can affect cartilage degradation. Diseased human cartilage and elephant dentine (positive control) were compared as substrates for osteoclasts. It has been observed by SEM that the cartilage surface around osteoclasts was damaged, suggesting their ability to degrade cartilage. The capacity of CD14+ monocyte-derived osteoclasts and primary human osteoclasts to release glycosaminoglycan and collagen from cartilage was observed in this thesis. Glycosaminoglycan release was reduced by both a pan-MMP inhibitor (GM6001) and TIMP1, suggesting that osteoclasts use soluble MMPs to degrade cartilage by release of proteoglycans. To find the key candidate(s), RT-qPCR and RNA sequencing were performed on osteoclasts cultured on plastic, dentine or cartilage. MMP- 8 and MMP-9 genes and proteins were highly expressed in osteoclasts on cartilage and gelatin zymography and siRNA experiments confirmed their activity and involvement in proteoglycan degradation. Finally, we confirmed the presence of MMP-8 and MMP-9 in tissue sections from conditions characterised by OA. This thesis highlights the morphological, immunophenotypic and gene expression differences when osteoclasts are cultured on different substrates. This thesis also highlights the necessity for contact between osteoclasts and cartilage for direct proteoglycan degradation whilst indirect interaction with osteoclasts degrading bone significantly decreases collagen release from cartilage. Direct and indirect chondrocyte and osteoclast co-culture experiments demonstrated the ability of chondrocytes to control osteoclast formation and activity, potentially via an increase in OPG and RANKL expression. Understanding and controlling the activity of osteoclasts might represent an interesting perspective for pathologies characterized by cartilage degeneration and would present an attractive target for further research.